2022
DOI: 10.1123/jsr.2021-0255
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest of a Novel Wii Board–Based Device to Assess Eccentric Knee Flexor Strength During the Nordic Hamstring Exercise

Abstract: This study aimed to assess the test–retest reliability of a Wii board–based device to assess the eccentric knee strength. Healthy participants (n = 20, 22.7 [3.4] y, 1.71 [0.09] m, 69 [13] kg) performed 2 assessments—days 1 and 2—of the Nordic hamstring exercise (3 trials per day, 3 min of rest between trials, and 48 h between trials) on a padded board with an attached Wii Balance Board (WBB). A ratchet inelastic strap made the contact between the participant’s distal aspect of both legs and the inverted upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Previous studies showed the WBB validity and reliability compared with a force platform, and the reliability of the Nordic exercise system using the WBB. 9,16 After an initial familiarization session and following a warm-up set of submaximal bilateral NHE (using an anchored elastic band to assist the exercise), the participants were asked to perform 3 trials of maximal NHE (actual NHE without any assistance with controlled velocity of execution using a digital metronome; 3 min of rest between trials was allowed). Each subject was asked to refrain from strenuous exercise or training 48 hours before assessments, and to avoid eating 2 hours before testing.…”
Section: Equipment and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed the WBB validity and reliability compared with a force platform, and the reliability of the Nordic exercise system using the WBB. 9,16 After an initial familiarization session and following a warm-up set of submaximal bilateral NHE (using an anchored elastic band to assist the exercise), the participants were asked to perform 3 trials of maximal NHE (actual NHE without any assistance with controlled velocity of execution using a digital metronome; 3 min of rest between trials was allowed). Each subject was asked to refrain from strenuous exercise or training 48 hours before assessments, and to avoid eating 2 hours before testing.…”
Section: Equipment and Proceduresmentioning
confidence: 99%
“…7 Other kinetic measurements using the Nordic curl are available using commercial or customized systems. 8,9 However, their lack of portability and the elevated cost (approximately $5000) may limit the use of their assessment for many coaches.…”
mentioning
confidence: 99%